Simultaneous use of alcohol and cocaine A qualitative investigation - Pakula, B.; MacDonald, S.; Stockwell, Tim; Sharma, R. (Informa Healthcare, 2009)
Objectives The objectives of this qualitative investigation are twofold 1 to clarify issues related to measuring simultaneous use in the context of alcohol and cocaine and 2 to explore the patterns of simultaneous use of cocaine and alcohol, focusing on temporal order, mode of administration, drug form, and drug dose. Methods Indepth openended pilot interviews with simultaneous cocaine and alcohol users were conducted at a residential treatment centre in Ontario, Canada n 10. The interview transcripts were coded by three coders independently. Analyses of the transcripts were performed to identify emerging themes and to develop conceptual networks of codes. Findings Respondents focused on the effects of introducing one substance after the other, rather than the combined effects of both alcohol and cocaine. They also discussed the importance of alcohol in relation to different methods of use, with alcohol being more common when cocaine was snorted, rather than injected or smoked. Finally, preliminary results suggest that the temporal order of cocaine or alcohol ingestion is related to differential functions of use. The study highlights the importance of developing better measures of patterns of simultaneous use to describe the complexity of alcohol and cocaine use and its effects. © 2009 Informa UK Ltd All rights reserved.